Occupational Stress In Medical Workers at Naibonat Hospital - Eta Pello; Marselino K. P. Abdi Keraf; R. Pasifikus Christa Wijaya; Noorce Berek (Universitas Nusa Cendana, 2021)
Abstract: Occupational stress is a condition in which the work demands exceed the workers' capabilities, resulting in various adverse reactions to the worker's physical, psychological, and behaviour. The inability to answer these demands is very likely a trigger for work stress, that work stress is a situation where a person faces a task or job that cannot or cannot be reached by his / her abilities. The purpose of this study was to determine the work stress of health workers (nurses, midwives and doctors) and to determine work stress based on aspects of work stress (physiological, psychological and behavioral) in health workers at Naibonat Hospital, Kupang Regency. This type of research is quantitative research. The total sample was 110 health workers, namely 51 nurses, 49 midwives and 10 doctors. In this study, using descriptive analysis to determine the work stress between nurses, midwives and doctors. The results of the descriptive analysis state that there is a comparison of work stress between nurses, midwives and doctors as well as aspects of work stress in terms of aspects (physiology, psychology and behavior) in health workers at Naibonat Hospital, Kupang Regency.